Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian (Studi Kasus Pada Umkm Kripik Tempe Mbak Enik Di Kota Purwodadi Kabupaten Grobogan) - Dwi Bagas Ma’a Shobirin; Sri Martono (LPPM Universitas An Nuur, 2023)
Background : Business competition is very tight where every entrepreneur wants to produce quality products, from the various similar products currently circulating, this means that business people must be able to survive and compete by producing quality products. Marketing products or services to consumers, in the business world which is designed to plan, determine prices, promote and distribute various products that are able to fulfill consumer desires with the aim of reaching the target market achieving the goals desired by the company. The good and bad of marketing management carried out encourages consumers to do so. buying decision. Purpose: To purpuse Product Quality, Price and Promotion on Purchasing Decisions (Case Study of Mbak Enik's Tempe Chip MSMEs in Purwodadi City, Grobogan Regency) Methods: This research uses a quantitative approach which aims to test the hypothesis formulated. Determining the number of samples used the Slovin formula with a purposive sampling technique and obtained a sample of 174 respondents. Analyzed using the Statistical Analysis Program for Social Science (SPSS) statistical analysis technique. Conclusion: The research results show that product quality has a significant influence on purchasing decisions, price has a significant influence on purchasing decisions. Promotions have a significant influence on purchasing decisions. And product quality, price and promotion simultaneously have a positive and significant influence on purchasing decisions. Suggestion: For future agendas, you can add research variables such as brand, consumer preferences, environmental factors, service quality, and other variables.